AUGMENTED REALITY PENGENALAN OBJEK 3D HARDWARE KOMPUTER DENGAN METODE MARKER BASED TRACKING - Kie, Yongky; Putri, Anggia (Computer Science and Industrial Engineering, 2022)
Along with technological advances, there are many media that can be used to support school children's learning, one of which is digital education media that can provide various learning methods so that students do not feel bored during the learning process. However, currently there are still many schools that have not used technology in the field of education that requires different methods, such as introduction to computer hardware in ICT subjects for junior high school students. Existing facilities in some schools are very limited and teachers still use conventional methods, namely using tools such as books or 2-dimensional pictures that are only shown to students but do not practice so that students do not have a broad understanding of information and uses regarding computer hardware. If Augmented Reality technology is applied in schools, students will be more interested in learning about this material because computer hardware objects can be displayed in 3D form. This study uses the Multimedia Development Life Cycle (MDLC) method, the Marker based tracking method which is used as a benchmark for displaying 3D objects and can be run on smartphones with the Android operating system. This application is made with several supporting applications such as Unity 3D, Vuforia, Adobe Photoshop, Blender 3D, Visual studio and the C# (C Sharp) programming language. The purpose of building this augmented reality application is to increase students' interest and enthusiasm for learning about computer hardware introduction material at the school level.